First molecular detection of Babesia vulpes and Babesia capreoli in wild boars from southern Italy - Sgroi, Giovanni; D’Alessio, Nicola; Auriemma, Clementina; Salant, Harold; Gallo, Amalia; Riccardi, Marita Georgia; Alfano, Flora; Rea, Simona; Scarcelli, Stefano; Ottaviano, Martina; De Martinis, Claudio; Fusco, Giovanna; et al. (Frontiers in Veterinary Science, 2023)
Introduction: Following the increase of wild boar (Sus scrofa) populations in Europe, a potential risk of emerging infections by vector-borne pathogens may occur. Despite this, the circulation of piroplasmid species in these ungulates is still a neglected topic, particularly in the Mediterranean basin.Therefore, this study aimed to investigate the presence of Babesia/Theileria spp. in wild boars from southern Italy to assess the epidemiological role of these ungulates in the circulation of piroplasmids. Methods: By using a citizen science approach among hunters and veterinarians, wild boar spleen samples were collected in the Campania region (southern Italy) between 2016 and 2022. A combined semi-nested PCR/sequencing analysis targeting the V4 hyper-variable region of 18S rRNA was run to detect Babesia/Theileria spp. DNA.Results: Out of 243 boars, 15 (i.e., 6.2%, 95% CI: 3.4 -9.9) tested positive to Babesia/Theileria spp., Babesia vulpes (n = 13, 5.3%, 95% CI: 3.1 -8.9) the most prevalent, followed by Babesia capreoli (n = 2, 0.8%, 95% CI: 0.2 -2.9). Three different B. vulpes sequence types were identified (i.e., ST1, ST2, ST3), with the most representative as ST1 (60%), and a single B. capreoli sequence type. No statistically significant difference (p > 0.05) was found between the presence of the pathogens and boar age, sex, province and sample collection year.: Data demonstrate for the first time the occurrence of B. vulpes and B. capreoli in wild boars, which may play a role in the biological cycle of piroplasmids. We emphasize the importance of monitoring these ungulates to prevent potential foci of infection. The engagement of hunters in epidemiological scientifically based surveys can constitute a technically sound control strategy of piroplasmids in a One Health perspective.